How does the market variance risk premium vary over time? Evidence from S&P 500 variance swap investment returns - Eirini Konstantinidi; George Skiadopoulos (The University of Manchester, Manchester Business School, 2014)
We explore whether the market variance risk premium (VRP) can be predicted. First, we propose a novel approach to measure VRP which distinguishes the investment horizon from the variance swap's maturity. We extract VRP from actual rather than synthetic S&P 500 variance swap quotes, thus avoiding biases in VRP measurement. Next, we find that a deterioration of the economy and of the trading activity, increase VRP. These relations hold both in- and out-of-sample for various maturities and investment horizons and they are economically significant. Volatility trading strategies which condition on the detected relations outperform popular buy-and-hold strategies even after transaction costs are considered.
Keywords: G13; G17; 330; Economic conditions; Predictability; Trading activity; Variance swaps; Variance risk premium; Volatility trading